P880 Dysbiotic changes caused by polyethylene glycol in ulcerative colitis patients: "Lavage" or intrinsic effect?. (16th January 2018) - Robles, V; Herrera-deGuise, C; Varela, E; Santiago, A; Campos, D; Pozuelo, M; Manichan, C; Casellas, F; Borruel, N; Guarner, F
Abstract: Background: Dysbiotic changes have been described in fecal microbiome composition in ulcerative colitis (UC) patients when compared with fecal microbiome of healthy individuals. It is not clear if these changes persist during remission periods. Some UC patients report a clinical relapse after a colonoscopy. We sought to evaluate the effect of polyethylene glycol (PEG) preparation on fecal microbiome of UC patients in clinical remission and healthy controls, through the application of 16S rRNA gene sequencing techniques. Methods: All subjects received identical standard colonoscopy preparation with PEG. Only the UC patients underwent surveillance colonoscopy required by their treating physician. Stool samples were collected at different time points: −30, -1 day (before bowel preparation), the first formed stool sample after bowel preparation, +15, +30 and +60 days. We performed 16S rRNA gene sequencing techniques by amplification of the variable region V4. We used Chao1 to estimate microbiome diversity. Results: Eleven UC patients in clinical remission and 12 Healthy controls (HC) were recruited. One hundred and thirty-seven samples were analysed. We obtained 3892300 high-quality sequences, with a mean base pair number of 314 and 558 Operational taxonomic Units (OTUs). At baseline, diversity in terms of Chao1 was significantly lower in UC patients compared with HC (Median: 132.3 vs. 188.2, p < 0.01). PEG induced a decline in Chao1 in both UC and HC subjects. The magnitude of this decrease was not different between the groups. The microbiome diversity returned to baseline levels at the +60 day time point. Neither Faecalibacterium prausnitzii (Fp) nor Escherichia coli ( E. coli ) abundance differed at baseline between the groups, however, after PEG, an decrease in Fp abundance was observed in UC patients while in HC FP levels were increased (median Fp −0.004 vs. 0.0025, p < 0.01). PEG had the opposite effect on E. coli abundance, with an increase in UC patients and a decrease in HC (Median E coli 0.0015 vs. −4.85 × 10 –5, p < 0.05). Akkermansia muciniphila (Akk) was not detected in any of the UC patients at any time point and in the HC group, Akk was measured in 7 out of 12 at baseline. After PEG preparation, it was just detected in 2 out of the 12 HC. Conclusions: PEG induces similar diversity changes in both UC and Healthy subjects, regardless of baseline diversity. In UC patients PEG has dysbiotic effects, mostly on Fp and E coli abundance. This may be due to a "lavage" effect of PEG, which could unmask an existing dysbiosis on the right colon of these patients, or secondary to a direct effect of PEG on the microbiome.